Design and regulation of balancing power auctions: an integrated market model approach - Karl-Martin Ehrhart; Fabian Ocker (Journal of Regulatory Economics, 2021)
We present an integrated market model which considers the dependencies between the wholesale market and the highly regulated balancing power markets. This fosters the understanding of the mechanisms of these markets and, thus, allows the evaluation of the designs of these markets and their interplay. In contrast to existing literature, in our model the prices on the different markets are interdependent and endogenously determined, which also applies to the switch from inframarginal suppliers to extramarginal suppliers. Linked to this, the implementation of a specific assignment of the suppliers to the different markets is according to their production costs and their ability to provide balancing power. We prove the existence of a market equilibrium, analyze its outcome and contrast this with German market data. Based on this model, we assess design changes, partly stipulated by recent European regulation. This includes uniform pricing as a common settlement rule (effect: no truthful bidding in general), standardized prequalification criteria (promising measure for cost reduction), market flexibilization via "free energy bids" (no increased competition) and the alternative score "mixed-price rule" (no effect on the equilibrium).
Keywords: D2; D4; D5; D6; L1; L5; 330; Balancing power; Market design and interdependence; Scoring rule; Settlement rule